The Role of GSK-3α Inhibition in Attenuating LPS-Induced Inflammation in RAW 264.7 Cells - Oyewole, Oluwaseyi (AUC Knowledge Fountain, 2025)
Glycogen synthase kinase-3 (GSK-3), an enzyme that modulates glucose metabolism, has been recognized as an essential target in major inflammatory diseases based on its great specificity in substrate recognition. GSK-3β has been connected to cancer, obesity, liver diseases, and neurological diseases. Nonetheless, the other GSK-3 isoform, GSK-3α, is much less studied. Previous studies from our laboratory showed that inhibiting GSK-3α potentially confers an anti-inflammatory response when tested on microglia. However, little has been documented regarding the exact mechanism by which GSK-3α exerts its effect. One of the potential mechanisms involving its anti-inflammatory effect could be partially attributed to activating the nuclear factor erythroid 2–related factor 2 (Nrf2) signaling pathway. This study examines whether the inhibition of GSK-3α confers an anti-inflammatory and antioxidant response independent of the Nrf2 pathway. Our result showed that inhibiting GSK-3α in LPS-stimulated RAW 264.7 cells downregulate nitrate production. Real-time PCR results indicated that inhibiting GSK-3α in LPS-stimulated macrophages attenuates the expression of the proinflammatory genes Tumor necrosis factor (TNF-α), inducible nitric oxide synthase (iNOS), and interleukin 6 (IL-6). Remarkably, at the translation level, the protein expression levels of iNOS and TNF-α were also denounced. Interestingly, our study provides further insight into the anti-inflammatory role of GSK-3α in post-transcriptional studies as evidenced in the downregulation of two mRNAs, in particular, miR-21 and miR-155, implicated in inflammatory-related diseases post GSK-3α inhibition. Our molecular assay showed that the Nrf2-regulated genes: Osgin1 (Oxidative Stress Induced Growth Inhibitor 1) and HO-1(Heme oxygenase-1) were upregulated in response to treatment with GSK-3α inhibitor when compared to their control counterparts. Collectively, our results indicate the role of GSK-3α in modulating inflammatory responses and suggest Nrf2 as a possible pathway that mediate the anti-inflammatory and antioxidant benefits of GSK-3α inhibition.